Numerical analysis of the influence of the impregnation ratio on the microporous structure formation of activated carbons, prepared by chemical activation of waste biomass with phosphoric(V) acid. (June 2017) - Kwiatkowski, Mirosław; Kalderis, Dimitrios; Diamadopoulos, Evan
Abstract: This paper presents the results of the application of new mathematical adsorption models with the unique numerical fast multivariate identification procedure as the tool for analysing the influence of the impregnation ratio i.e. activator to the raw material mass ratio on the microporous structure development of the activated carbons, obtained from sugarcane bagasse and rice husk by chemical activation with phosphoric(V) acid. Highlights: Analysis of the effects of the impregnation ratio on the microporous structure formation were carried out. The new mathematical adsorption models, with the unique numerical fast multivariate identification procedure were used. The LBET class models yielded detailed and comprehensive information on the analysed structure of the activated carbons.